2013
DOI: 10.4155/bfs.12.77
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing hammer mill performance through screen selection and hammer design

Abstract: Background: Mechanical preprocessing, which includes particle-size reduction and mechanical separation, is one of the primary operations in the feedstock supply system for a lignocellulosic biorefinery. It is the means by which raw biomass from the field or forest is mechanically transformed into an on-spec feedstock with characteristics better suited for the fuel conversion process. Results: This work provides a general overview of the objectives and methodologies of mechanical preprocessing and then presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 24 publications
(13 reference statements)
1
21
0
2
Order By: Relevance
“…The SER and SFU for grinding bales were greater than for baling of chopping. The SFU reported here is in the same range as that reported for SWG and CS bales when throughputs were similar to those found here [40]. When LRBe throughputs varied from 10 to 45 Mg·h −1 , SFU of tub grinding with screen sizes similar of those used here were 5.9 to 9.7 L·Mg −1 for CS and 2.6 to 3.4 L·Mg −1 for NTG [41].…”
Section: Bale Grinding and Shreddingsupporting
confidence: 85%
See 1 more Smart Citation
“…The SER and SFU for grinding bales were greater than for baling of chopping. The SFU reported here is in the same range as that reported for SWG and CS bales when throughputs were similar to those found here [40]. When LRBe throughputs varied from 10 to 45 Mg·h −1 , SFU of tub grinding with screen sizes similar of those used here were 5.9 to 9.7 L·Mg −1 for CS and 2.6 to 3.4 L·Mg −1 for NTG [41].…”
Section: Bale Grinding and Shreddingsupporting
confidence: 85%
“…Previous research on tub grinding biomass has been done with LRBes or CD LSBes and the reported throughputs and SFU varied considerably across these studies [39][40][41][42]. Based on the results here and those of previous research, only estimates of SFU to grind HD LSBes can be made.…”
Section: Discussionmentioning
confidence: 84%
“…However, crushing degree of the olive paste depends on the energy transferred to the olives during the crushing operation, which is mainly affected by the retention time inside the hammer mill . We propose that open area (i.e., the percentage of the area of holes over the total area of the screen) should be also considered in screen characterization, since it has proven to have an effect on the retention time and crushing degree during the processing of other matrixes . Herein, we built upon our earlier work to study the impact of sieve design (screen size and open area) and rotor speed on extraction efficiency, quality and minor components composition of olive oil at a laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…There, it was processed using the pilot-scale feedstockhandling unit operated by INL as described by Yancey et al [16] and hammer milled to pass through a 1.9 cm (0.75 in.) round rejection screen.…”
Section: Feedstockmentioning
confidence: 99%